2017
DOI: 10.14198/jhse.2017.123.07
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence, self-determined motivation and performance in canoeists

Abstract: The results of recent studies indicate that athletes differ in the degree in which they perceive, process and regulate their emotions. The present study aims to utilize these findings in order to examine if self-determined motivation in sport could explain individual variations in emotional intelligence (EI) and results of sport competitions. A model of structural equations has proven these relationships in 386 canoeists from 35 countries. These results support the mediating factor of EI in relation to autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…The high EI cluster was associated with the most self-determined types of regulation. The results were also consistent with literature regarding correlations of the three factors of EI with self-determined motivation (Arribas-Galarraga et al, 2017;Cera et al, 2015), although values higher than those obtained in different studies emerged. Students with higher EI tend to be regulated in an intrinsic and identified way, that is, they participate in class activities because they consider them enjoyable and interesting, and these activities fit their personal goals (e.g., Spence, Oades, & Caputi, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high EI cluster was associated with the most self-determined types of regulation. The results were also consistent with literature regarding correlations of the three factors of EI with self-determined motivation (Arribas-Galarraga et al, 2017;Cera et al, 2015), although values higher than those obtained in different studies emerged. Students with higher EI tend to be regulated in an intrinsic and identified way, that is, they participate in class activities because they consider them enjoyable and interesting, and these activities fit their personal goals (e.g., Spence, Oades, & Caputi, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In the educational context, Perrault, Mask, Morgan, and Blanchard (2014) found positive, moderate correlations between EI General Index and General Self-Determination Index in a sample of Canadian university students. In the sport context, positive and low correlations have been reported between the factors of EI (recognition, control and regulation, and emotional empathy) and autonomous motivation in canoeists from 35 different countries (Arribas-Galarraga, Saies, Cecchini, Arruza, & Luis-De-Cos, 2017). In the PE context, Cera, Almagro, Conde, and Sáenz-López (2015) reported positive and low correlations but only between emotional attention and repair dimensions and intrinsic motivation and identified regulation.…”
Section: Motivation and Emotional Intelligencementioning
confidence: 99%
“…In our study, EI showed no statistically significant differences in training duration (p > .05). Similar results were obtained by Arribas-Galarraga et al (2017), who observed that the EI of rowers remains relatively stable regardless of years of practice. Peña-Sarrionandia, Mikolajczak, and Gross (2015) point out that individuals with high EI successfully regulate their emotions when needed, and they do it flexibly, leaving space for emotions to emerge and express.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, recent studies uncovered a strong linkage between emotional intelligence and job & organizational performance (Pekaar, Linden, Bakker & Born, 2017;Abraham, 2004;Jorfi, Jorfi & Moghadam, 2010;Higgs, 2004;Codier, Kamikawa, Kooker & Shoultz, 2009;Arribas-Galarraga, Saies, Cecchini, Arruza & Cos, 2017;Chaudhry & Usman, 2011). Emotional intelligence equips individuals with the skills to anticipate their performance, especially in teamwork (Offermann, Bailey, Vasilopoulos, Seal & Sass, 2004).…”
Section: Emotional Intelligence and Organizational Performancementioning
confidence: 99%